Food security and sustainable growth for pastoral systems in semi-arid Africa - Webb, P.; Bisrat, G.; Coppock, D. Layne (German Foundation for International Development, 1991)
This paper explores the potential for, and limits to, sustainable agricultural growth in semi-arid Africa, with a focus on the role of pastoralism. Examines the main pressures on pastoral systems, and on the resource base upon which these depend. The paper argues that it is premature to contemplate sustainable growth until current trends in both human and biological resource degradation have been halted and reversed. Following an outline of concepts, the key features of African pastoralism are described. The third section of the paper examines the constraints on such systems, highlighting linkages between pressures on pastoralism and those on the pastoral resource base. Major strategies adopted by pastoralists in the face of increasing pressures are summarized in the fourth section. Finally, two major conclusions deriving from the analysis are presented, and these are 1. A new focus is needed on increasing inputs to pastoralism rather than on outputs, and 2. Sucess in reducing economic and environmental losses can only be sustained with a parallel reduction in the loss of human resources.